The role of networks in technological capability: A technology-based companies perspective - Cleonir Tumelero; Roberto Sbragia; Felipe Mendes Borini; Eliane Cristina Franco (Journal of Global Entrepreneurship Research, 2018)
This study examined the influence of networks on the development of technological capabilities of 90 technology-based companies (TBCs) graduated by Brazilian incubators. The relational-based view theoretically supported the study. The data were processed via Structural Equation Modeling (SEM). A model with three hypotheses was tested. Two hypotheses were validated, proving that technological and financial networks built by those firms with external agents explained 70.6% of their capacity to innovate. The insertion into technology networks of licensing, universities, suppliers, and consulting shows that the TBCs are making use of relationships of high technical content, which is expected according to previous literature. As for the financial networks, it was observed that the insertion into networks of venture capital and economic subvention demonstrates that the innovation ecosystem presents advancements in the well-known challenge of financial support for technology-based startups. A third hypothesis was not validated, which provides another important finding: the planning effort presented a negative relationship on the technological capability, but a positive relationship on the insertion into relationship networks. This means that only direct planning is not able to support technological capabilities. In other words, planning is more effective when indirectly applied to relational resources of technical and financial networks, rather than when directly applied to technological capabilities. The insertion into technical and financial networks, in turn, positively affects the TBC's innovation capability. Results demonstrate that this change in planning focus, from inside to outside of the company, could improve technological capabilities in R&D, patent, people, and products. Future studies could investigate the entrepreneur's competencies in managing networks and further understanding of how networks could be constructed through formal and informal cooperation.
Keywords: 650; Technology-based companies; Relationship networks; Technological capability; Small business; Entrepreneurship; Startups